Signatures of a quantum critical endpoint in the Kitaev candidate Na2Co2TeO6 - Arneth, Jan Victor; Choi, Kwang-Yong; Kalaivanan, R.; Sankar, Raman; Klingeler, Rüdiger (Physical review, 2024)
The putative Kitaev material Na2⁢Co2⁢TeO6 has recently been proposed to enter a quantum spin disordered state when magnetic fields are applied in parallel to the honeycomb layers. In this Letter we uncover signatures of a quantum critical endpoint (QCEP) associated with the assumed order-disorder transition by means of high-resolution capacitance dilatometry. At the critical field 𝐵C ≃6 T, a sign change of the out-of-plane thermal expansion coefficient 𝛼c indicates the accumulation of entropy upon crossing the phase boundary. The proportional relationship between isothermal magnetization and magnetostriction signals that the QCEP can be tuned by magnetic field and pressure simultaneously. The presented results expand the material classes that exhibit metamagnetic quantum criticality to honeycomb antiferromagnets with possible Kitaev interactions.